Are Islamic Boarding Schools Ready? The Use of the Computer-Based Test in the National Exam Policy for English Subject - Eka Septiarini Carolina (Ta'dib: Jurnal Pendidikan Islam, 2017)
The question of “Are Islamic boarding schools ready for using the computer-based test in the national exam policy? is interesting and challenging. Looking at the various conditions of Islamic boarding schools throughout Indonesia, the use of the computer-based test in the national exam policy for English subject is challenging for santris and ustazd (teachers). It is challenging because Islamic boarding schools are characteristically underprivileged and santris live in disadvantaged conditions under firm rules. The purpose of this paper is to discuss the use of the computer based test in the national examination for English subject at Islamic boarding schools. In this paper, I will discuss about the characteristics of English examination, the national examination policy in Indonesia, the national examination with computer based test, and the national examination in Islamic boarding school, and whether Islamic boarding schools are ready for using the computer-based test in the national exam policy for English subject.